Business Ethics in Islamic Stores: A Comparison of Perceptions Based on Gender and Student Areas of Study - Fitriana, Nabilla; Dewi, Novi Yanti Sandra; Agustina, Ahadiah (ITB AAS INDONESIA Surakarta, 2024)
The role of Islamic business ethics plays a significant part in shaping the perspectives of individuals or enterprises engaged in business activities. Therefore, the objective of this research is to explore the comparative perceptions of university students, considering gender and field of study, regarding the business ethics applied in Islamic-based retail businesses in the city of Mataram. The research employs a quantitative comparative method with a sample of 148 students, comprising 41 male and 107 female participants. The research instrument utilized is a Likert scale questionnaire consisting of six statements based on Islamic business ethics indicators, including monotheism (tauhid), responsibility, honesty, justice, and balance. The data analysis technique involves an independent t-test with two iterations: one testing based on the gender of students (male and female) and the other based on their field of study (economic and non-economic disciplines). The results of the data analysis reveal a t-test value of 0.847 for gender testing, with a significance level of 0.398>0.05. Similarly, the t-test value for the field of study is 0.801, with a significance level of 0.424>0.05. Therefore, the researcher concludes that there is no significant difference in the perceptions of students, both based on gender and field of study, regarding the Islamic business ethics applied by managers of Islamic retail stores in Mataram.